(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Human Resource Management (HRM) practices play a crucial role in the success of any organization, including educational institutions. This study investigates the impact of HRM on Madurai Diraviyam Thayumanavar Hindu College (MDTHC), Pettai, a reputed institution in Tamil Nadu, India. The abstract will explore how MDTHC’s HRM practices influence various aspects of the college, including: • Faculty recruitment and development: How HRM strategies attract, select, and train qualified teachers, impacting the quality of education. • Employee motivation and engagement: How HRM practices motivate staff, leading to a more productive and positive work environment. • Student performance and satisfaction: How effective HRM practices can indirectly improve student learning outcomes and satisfaction through a strong faculty and staff.